2021
DOI: 10.3390/ma14102563
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Micro-Structuring and Surface Smoothing of Additive Manufactured Parts Using DLIP Technique and Its Influence on the Wetting Behaviour

Abstract: It is well known that the surface topography of a part can affect its function as well as its mechanical performance. In this context, we report on the surface modification of additive manufactured components made of Titanium 64 and Scalmalloy®, using Direct Laser Interference Patterning technique. In our experiments, a nanosecond-pulsed near-infrared laser source with a pulse duration of 10 ns was used. By varying the process parameters, periodic structures with different depths and associated roughness value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…This can be explained by the different material properties (e.g., thermal conductivity) of titanium and aluminum alloys, which affect the formation of the periodic structures. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This can be explained by the different material properties (e.g., thermal conductivity) of titanium and aluminum alloys, which affect the formation of the periodic structures. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…The reason for taking the measurements after this period of time was because previous studies had already shown that the WCA significantly increases after the laser process until an equilibrium state is reached due to deposition from carbon on the surface from ambient air. [ 23 ] The diagrams include the obtained results with (orange area) and without (blue area) the application of Mecasurf for all surface conditions. The application of Mecasurf allows to elucidate the effects only related to surface topography, as in this case all samples have exactly the same surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations